1997
DOI: 10.1038/387308a0
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity and unfolding of single molecules of the giant muscle protein titin

Abstract: The giant muscle protein titin, also called connectin, is responsible for the elasticity of relaxed striated muscle, as well as acting as the molecular scaffold for thick-filament formation. The titin molecule consists largely of tandem domains of the immunoglobulin and fibronectin-III types, together with specialized binding regions and a putative elastic region, the PEVK domain. We have done mechanical experiments on single molecules of titin to determine their visco-elastic properties, using an optical-twee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
570
1
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 712 publications
(603 citation statements)
references
References 23 publications
28
570
1
4
Order By: Relevance
“…The polystyrene beads used in the tweezers are much larger (radius of curvature ~500 nm or bigger) than an typical AFM tip (radius of curvature ~10 nm) and therefore more space between the ends of the sample is required to avoid non-specific interactions between the tethering surfaces. Until the approach reported here (and used in Cecconi et al 2005), the only proteins amenable to study with the optical tweezers have been micrometer-long molecules naturally organized in linear arrays of hundreds of globular domains, such as titin (Tskhovrebova et al 1997;Kellermayer et al 2000). These experiments have revealed important aspects of the overall mechanical properties of these molecules, but failed to provide information on specific domain behavior due to heterogeneity of these naturally occurring polymers.…”
Section: Discussionmentioning
confidence: 99%
“…The polystyrene beads used in the tweezers are much larger (radius of curvature ~500 nm or bigger) than an typical AFM tip (radius of curvature ~10 nm) and therefore more space between the ends of the sample is required to avoid non-specific interactions between the tethering surfaces. Until the approach reported here (and used in Cecconi et al 2005), the only proteins amenable to study with the optical tweezers have been micrometer-long molecules naturally organized in linear arrays of hundreds of globular domains, such as titin (Tskhovrebova et al 1997;Kellermayer et al 2000). These experiments have revealed important aspects of the overall mechanical properties of these molecules, but failed to provide information on specific domain behavior due to heterogeneity of these naturally occurring polymers.…”
Section: Discussionmentioning
confidence: 99%
“…The initial experiments showed that, upon application of force, the multimodular protein titin unfolds one domain at a time. 1,3 Similar experiments on a number of proteins have verified that unfolding at the single molecule level can be monitored by subjecting the folded proteins to tension. 4,[7][8][9][10] The AFM experiments, which showed the characteristic sawtooth pattern in the force-extension (f -z) curves, were interpreted using the wormlike chain (WLC) model for the domains.…”
Section: Introductionmentioning
confidence: 94%
“…Hysteresis during Stretch-Release Cycles. The stretching of titin by optical tweezers 2,3 showed that when the unfolded protein is released, the molecule does not spontaneously refold. Upon decreasing the force, its extension initially decreases by about 50% compared to the fully stretched state.…”
Section: Distribution Of Unfolding Free Energy Barriers Atmentioning
confidence: 99%
See 2 more Smart Citations